The Prospects for Vietnamese Academic Library Consortia: Results of a Survey - Hoang, T.; Genoni, Paul (De Gruyter Saur, 2017)
© 2017 Walter de Gruyter GmbH, Berlin/Boston.Consortia are widely used by academic libraries worldwide to support the most cost-effective means of acquiring digital content and services. Some developing countries, however, have been slow to benefit from consortia due to a range of obstacles and challenges faced by their academic libraries and higher education sectors more broadly. This paper investigates the current state, and future prospects, for consortia in one developing country, Vietnam. A questionnaire survey was distributed to all academic libraries in Vietnam. Valid surveys were received from 99 respondents (34.37 % response rate). The survey results address a number of issues, including current levels of engagement in consortia; identification of drivers for, and obstacles to, the use of consortia; the support required by libraries for future participation; and the need for a supportive legal and administrative framework. The paper concludes that there is a willingness by Vietnamese academic librarians to engage with consortia, but there are also considerable obstacles to be overcome to make this possible. The conclusions are presented as a series of 11 recommendations aimed at improving the operating conditions for consortia in Vietnam.